2010
DOI: 10.1094/pdis-94-5-0642a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Pseudoperonospora cubensis Causing Downy Mildew of Trichosanthes cucumerina in Malaysia

Abstract: In December 2008, infected leaves of Trichosanthes cucumerina were observed on commercial cucurbit farms located in Pontian, Johor (south of West Malaysia). Bright yellow and small necrotic lesions were observed on the adaxial surface of the leaves, whereas sporangiophores were observed on pale yellowish brown-to-brown lesions on the abaxial surface. The length and width of the sporangia ranged from 19 to 36 μm (28.6) and 11 to 23 μm (17.6), respectively. The length of the sporangiophores ranged from 310 to 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recently, the occurrence of P. cubensis on some weedy and cultivated Cucurbitaceae was published (Choi and Shin 2008;Ko et al 2008;Salti et al 2010). Laboratory experiments demonstrated that P. cubensis can infect Bryonia dioica, the only perennial plant of the Cucurbitaceae in Central and Northern Europe.…”
Section: Host Rangementioning
confidence: 99%
“…Recently, the occurrence of P. cubensis on some weedy and cultivated Cucurbitaceae was published (Choi and Shin 2008;Ko et al 2008;Salti et al 2010). Laboratory experiments demonstrated that P. cubensis can infect Bryonia dioica, the only perennial plant of the Cucurbitaceae in Central and Northern Europe.…”
Section: Host Rangementioning
confidence: 99%
“…2010). Symptoms of cucurbit downy mildew were first reported on Trichosanthes cucumerina in Malaysia in 2008 (Salati et al. 2010).…”
Section: Discussionmentioning
confidence: 99%